(untitled) (Canadian Dermatology Today, 2025)
Tattooing of the skin is an age-old practice that involves delivering pigments to the dermis. Tattoos can be a mark of honour or status in specific cultures, a long-lasting reminder of a moment in time, or more simply a decorative feature of self-expression. Occasionally, tattoos can become painful reminders of moments past, such as a radiation tattoo years after remission from cancer, a lover’s name from a failed relationship or a tattoo from a gang affiliation/imprisonment/human trafficking. On a more mundane note, a tattoo can become out of fashion or individual taste may change over the years. “Tattoo regret” is very common and many patients seek out options to remove tattoos. Though historically, surgical techniques were required to remove tattoos, pigment-targeting lasers have become the first‑line treatment. Successful and safe laser tattoo removal requires a thorough understanding of treatment principles, appropriate laser wavelength selection, relevant biological endpoints, and prognostic factors that may guide the expected number of treatment sessions needed for a satisfactory outcome.